2017
DOI: 10.3899/jrheum.161125
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Screening Tests for Cognitive Impairment in Systemic Lupus Erythematosus

Abstract: CI is highly prevalent and MoCA may be a useful tool to screen for CI in SLE. Patients with more years of education were less likely to have CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 30 publications
6
53
4
1
Order By: Relevance
“…In our study, the MoCA test was the screening instrument that identifie the largest number of patients with cognitive impairment, followed by the MMSE and CSI, similar to the findings of previous reports. 10 , 21 – 23 In addition, the three instruments correlated with the gold standard neuropsychological battery findings, in the same order (MoCA > MMSE > CSI), providing concurrent validity. Our study is robust, as the application of all three screening tools for assessing cognitive impairment as compared to the gold standard has not been reported previously.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…In our study, the MoCA test was the screening instrument that identifie the largest number of patients with cognitive impairment, followed by the MMSE and CSI, similar to the findings of previous reports. 10 , 21 – 23 In addition, the three instruments correlated with the gold standard neuropsychological battery findings, in the same order (MoCA > MMSE > CSI), providing concurrent validity. Our study is robust, as the application of all three screening tools for assessing cognitive impairment as compared to the gold standard has not been reported previously.…”
Section: Discussionmentioning
confidence: 78%
“…Nantes et al conducted a study in 98 patients with SLE, in which the MoCA and MMSE were compared against the Hopkins Verbal Learning Test-Revised. 10 The MoCA test showed the highest sensitivity, while the MMSE presented highest specificity. In our study, the highest sensitivity and specificity were obtained with the MoCA test.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We read with great interest the paper on performance of screening tests for cognitive impairment (CI) in systemic lupus erythematosus (SLE), by Nantes, et al 1 . They indicated that CI is highly prevalent in SLE, and that the Montreal Cognitive Assessment (MoCA) is a good tool to screen early CI.…”
Section: Montreal Cognitive Assessment and Magnetic Resonance Imagingmentioning
confidence: 99%